2015
DOI: 10.1039/c5ra15381f
|View full text |Cite
|
Sign up to set email alerts
|

Application of gas chromatography-mass spectrometry and chemometrics methods for assessing volatile profiles of Pu-erh tea with different processing methods and ageing years

Abstract: 25Volatile changes and the post-fermentation ageing process of tea remain largely unknown. Additionally, 26 the understanding of the ageing and storage processes of tea mostly rely on sensory experience and 27 lack the support of scientific and accurate data. In this paper, a development method based on the 28 head-space solid phase microextraction/gas chromatography-mass spectrometer (HS-SPME/ GC-MS) 29 combined with multivariate statistical methods was used to assess volatile profiles in different type 30 Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…The 6-methyl-5-heptane-2-one was described as sweet, fruity, with orange odor notes, and previous studies confirmed that the compound showed an increasing trend in the processing of Oolong tea [9,38]. Regarding acetophenone, it was identified in Oolong tea [39], green tea [40], Pu'er tea [41] and Jasmine tea [27], but had little effect on the tea aroma. Moreover, there was a negative correlation between the relative content of 6-methyl-5-hapten-2-one and the quality grade.…”
Section: Ketonesmentioning
confidence: 93%
“…The 6-methyl-5-heptane-2-one was described as sweet, fruity, with orange odor notes, and previous studies confirmed that the compound showed an increasing trend in the processing of Oolong tea [9,38]. Regarding acetophenone, it was identified in Oolong tea [39], green tea [40], Pu'er tea [41] and Jasmine tea [27], but had little effect on the tea aroma. Moreover, there was a negative correlation between the relative content of 6-methyl-5-hapten-2-one and the quality grade.…”
Section: Ketonesmentioning
confidence: 93%
“…The volatile compounds were identified by comparing their mass spectra with those of the mass spectra libraries NIST 08 and Wiley 7. Additionally, a series of n-alkanes (C 8 –C 40 ) were run under the same chromatographic conditions to calculate the RIs of detected compounds by comparing them with the RIs provided by the NIST Chemistry Web Book ( http://webbook.nist.gov/chemistry/ ) and in previous literature [ 31 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it can extract relevant information and discover patterns in large series of data [16]. The most frequently used chemometric methods, including PCA [17], PLS-DA [13], and HCA [17], have been confirmed to be efficient and rapid methods to highlight differences among tea samples [18][19][20]. PCA is based on the concept of dimensionality reduction to transform multiple indicators into a few comprehensive ones, thereby simplifying the analysis process [21][22][23].…”
Section: Introductionmentioning
confidence: 99%